Analysis of the Effect of Budget Efficiency on Fiscal Resilience - Kusuma, Wennie Candra; Bintoro, Nugroho Suryo (Journal of Development Economic and Social Studies, 2026)
The central government's budget efficiency policy, which cuts transfers to regions by Rp50.59 trillion in 2025, poses serious challenges to regional fiscal resilience, especially in East Java. This study analyzes the impact of Local Own Revenue, economic growth, Transfers to Regions, and regional characteristics on fiscal independence in 38 districts/cities in East Java using data from BPS and DJPK for Quarter I/2024 to Quarter II/2025 with Two-Step System GMM approach. Results show that Local Own Revenue has a significant positive effect with elasticity of 0.185, economic growth has positive but statistically insignificant effect, budget efficiency through reduction of Transfers to Regions increases short-term fiscal independence with negative coefficient of 0.197, and districts have 1.9 percent higher fiscal resilience than cities due to transmigration effect. High fiscal persistence with lag coefficient of 0.451 indicates that improving fiscal resilience requires consistent long-term strategy. Simulations show that continuous efficiency of 5 percent per quarter can reduce fiscal resilience below crisis threshold within three quarters, while minimum economic growth threshold of 4.31 percent per year is needed to maintain fiscal independence amid budget efficiency policies.